Socio-demographic Determinants and the Family Ability to Care for Children with Avoidant Restrictive Food Intake Disorder (ARFID) - Yoyok Bekti Prasetyo; Nursalam Nursalam; Rahmat Hargono; Ahsan Ahsan (Universitas Airlangga, 2019)
Background: The ability of families to care for avoidant restrictive food intake disorder children is still low. There is only few studies that examined relationship between family factor to ability to care children with avoidant restrictive food intake disorder. The purpose of this study was to identify the influence of socio-demographic factors on the ability of families to represent children with avoidant restrictive food intake disorder.Method: The study design was cross-sectional, and the majority of samples were gathered using the rule of the thumb, totaling 245 participants. The sampling technique used a type of multistage sampling. Data were collected by questionnaire. We then conducted an analysis of the univariate data using frequency distribution, while for the bivariate data, we used the chi-square technique. All of the data was processed using IBM SPSS 23.0 statistics.Results: The results showed that the ability of care from the families (health promotion behavior) of children with avoidant restrictive food intake disorder was influenced by the socio-demographic factors, namely maternal age (p= 0.010), the number of children (p= 0.047) and education (p= 0.036).Conclusion: Young mothers need appropriate guidance and direction through good health education. Good health education in young mothers can reduce the pressure faced by the mothers when caring for their children with avoidant restrictive food intake disorder. Health promotion behavior is influenced by maternal education and maternal age. Through good mother's education, the mother will be able to provide a good pattern of care to children who experience avoidant restrictive food intake disorder.